2012
DOI: 10.1021/jo3014879
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Interconversions of Pd and/or Au Bis-Metalated [32]Octaphyrins(1,0,1,0,1,0,1,0) Involving Hückel and Möbius Macrocyclic Topologies: A Theoretical Prediction

Abstract: Several Pd and/or Au bis-metalated [32]octaphyrins(1,0,1,0,1,0,1,0) were theoretically designed with rich conformations of Hückel or Möbius topology. The conformations and hence properties of macrocycles were tuned by twisting the active pyrrolic ring either clockwise (through multistep reactions with several Hückel and Möbius macrocyclic intermediates) or anticlockwise (via a direct Hückel-Hückel chiral interconversion). The encapsulated metal atoms, M(1), M(2) = Pd, Au, give different impacts on these two re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…They confirmed that the complex adopts a figure-eight structure with weak antiaromaticity by spectroscopic analyses and density functional theory (DFT) calculations. Our previous theoretical prediction about the aromaticity of this compound is basically in agreement with their assertion . Moreover, using free-based [32]­octaphyrin(1.0.1.0.1.0.1.0) with multiple conformers involving Hückel and Möbius topologies, we have demonstrated that the conclusions from some numerical indexes of aromaticity, such as the Julg parameter (Julg A), harmonic oscillator model for aromaticity (HOMA), magnetic susceptibility exaltations (Λ), and nucleus-independent chemical shift (NICS), are perfectly matched with each other.…”
Section: Introductionsupporting
confidence: 83%
“…They confirmed that the complex adopts a figure-eight structure with weak antiaromaticity by spectroscopic analyses and density functional theory (DFT) calculations. Our previous theoretical prediction about the aromaticity of this compound is basically in agreement with their assertion . Moreover, using free-based [32]­octaphyrin(1.0.1.0.1.0.1.0) with multiple conformers involving Hückel and Möbius topologies, we have demonstrated that the conclusions from some numerical indexes of aromaticity, such as the Julg parameter (Julg A), harmonic oscillator model for aromaticity (HOMA), magnetic susceptibility exaltations (Λ), and nucleus-independent chemical shift (NICS), are perfectly matched with each other.…”
Section: Introductionsupporting
confidence: 83%
“…The equilibrium constants ( K 298.15 ) of Hückel–Möbius isomerization for three systems with different sizes are calculated to be 0.18, 3.95, and 3.68, respectively. The large reaction rate and the comparable population of the isomers in Hückel-to-Möbius transformations indicate that the two conformers are easily converted to each other and can maintain dynamic balance under normal conditions, as observed in macrocyclic expanded porphyrins. , , …”
Section: Resultsmentioning
confidence: 99%
“…Some recent works have studied Hückel's rule from the perspective of electron delocalization [58,59]. Since the studies of Hückel on organic molecules, the concept of aromaticity has extended importantly including all sorts of new aromatic molecules such as metalloaromatic molecules [4,51,52,60,61], fullerens [62], nanotubes [63], porphyrins [64,65] with a Möbius-like structure [66][67][68][69][70][71][72][73], and all-metal clusters [4,5], among others.…”
Section: Hückel Molecular Orbital Methodsmentioning
confidence: 99%